(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
In this paper a single mode fiber have been chosen with a refractive index (1.50) to the core, and (1.485) to the cladding, with length of (2 m). It was exposed this optical fiber to a bending with different diameters, and to a different temperatures as well as pressure due to putting different weights to study dispersion phenomenon which affects on a pulse shape that travels in optical fiber. Experimental results explain when a bending diameter for an optical fiber increases it will decrease the dispersion and pulse shape will approximate from a Gaussian shape , and the increasing in temperature will increasing the attenuation in the pulse transfer through the optical fiber . But when increasing pressure, the dispersion will increases and the pulse shape will be distorted